Putting oneself in the shoes of another: issues of empathy and intercultural understanding in the Australian geography curriculum. Issue 4 (2nd October 2017) - Harrison, Neil
ABSTRACT: Geography is about the places that make up the world. A key focus of the new geography curriculum in Australia is on different ways of finding knowledge about those places. Yet there is limited demonstration in the curriculum and its elaborations of just how students might understand those places outside the realm of their own experience. In presenting geography education as a study about places, students (and teachers) are positioned as those who manage the order and balance of a human-centred world. Places are made to appear "useful" and profitable, always the object of study. I suggest that the onto-epistemic assumptions built into the Australian geography curriculum make it difficult for students and teachers to understand Aboriginal and Torres Strait Islander concepts of place outside their own experiences. Invoking notions of empathy throughout the curriculum as a means for working across differences is fraught by our limited ability to observe and listen beyond our own experience. Whilst it is argued that putting oneself in the shoes of another is a dangerous activity, empathy does create certain ethical possibilities around self-reflection and moral obligation.